Clinical factors associated with quality of life among women with endometriosis: a cross-sectional study - Karin Pontoppidan; Matts Olovsson; Hanna Grundström (BMC, 2023)
Abstract Background Endometriosis often leads to a decrease in Quality of Life (QoL), due to its impact on various aspects of women's lives, such as social life, mental health, sex life, and working capacity. Although previous studies have assessed QoL in women with endometriosis, few studies have explored the impact of different clinical variables on QoL. The aim of this study was to investigate how women with endometriosis perceive their QoL, and to analyze which clinical factors are associated with QoL. Methods The Endometriosis Health Profile-30 and the ENDOCARE Questionnaire were distributed to 1000 women diagnosed with endometriosis from 10 different clinics across Sweden. The responses from 476 women were included in univariate and multivariable regression analyses, where the clinical factors were correlated with overall QoL and QoL dimensions. Results The women participating in this study reported a low QoL. The clinical factors that showed a significant correlation with overall QoL were age at first onset of endometriosis symptoms (β= -0.64, p < 0.001), having more than 10 visits to general practitioners before referral to a gynecologist (β = 5.58, p = 0.036), current or previous mental health issues (β = 7.98, p < 0.001) patient-centeredness (β= -2.59, p < 0.001) and use of opioids (β = 7.14, p = 0.002). Conclusions This study shows that opioid use and mental health issues were associated with a worse QoL, whereas a higher degree of patient-centeredness was associated with a better QoL. The association between opioid use and a worse QoL might not entirely be caused by the opioid use itself but also by symptom severity and mental health issues. An improved patient-centeredness and more focus on taking care of mental health issues would reasonably result in a better QoL for women with endometriosis.